INTEROPERABILITY AND COMPATIBILITY OF ELECTRONIC MEDICAL RECORDS IN ENHANCING HEALTHCARE SERVICE QUALITY: A CASE STUDY AT DR. ABDUL AZIZ REGIONAL HOSPITAL, SINGKAWANG - Aprisipa, Aprisipa; Zulfikar, Taufik; Sofia Mariati Asnar, Etty (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The implementation of Electronic Medical Records (EMR) in hospitals is a strategic step toward improving the quality of healthcare services. However, compatibility and interoperability issues with external systems remain major challenges, particularly in regional hospitals. This study aims to analyze the compatibility and interoperability of the EMR system at RSUD dr. Abdul Aziz Singkawang, as well as its impact on service quality. It also addresses research gaps concerning the lack of in-depth studies on technical barriers and infrastructure limitations in EMR implementation. Using a descriptive case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that while the EMR system is compatible with most internal hospital systems, it faces significant interoperability challenges with external platforms, mainly due to data format discrepancies and limited IT infrastructure. Nevertheless, EMR implementation has successfully improved administrative efficiency, reduced documentation errors, and enhanced the quality of patient services. This study contributes to the literature on health information system integration in regional hospitals and recommends improving system interoperability and upgrading IT infrastructure as strategic actions to support the digital transformation of healthcare services.